Case report: Thoracic vertebral abscess caused by Salmonella via diagnosed next-generation sequencing - Cao, Xiao-guang; Ni, Jun-xi; Huang, Chong-jian (Frontiers in Medicine, 2024)
The genus Salmonella consists of Gram-negative bacteria with various serotypes. It commonly causes bacterial infections that affect the intestines. Infection can occur in humans and animals through the ingestion of contaminated food or water, or through contact with infected animals or environments. Complications commonly include intestinal hemorrhage and perforation, though vertebral osteomyelitis is rarely observed. Therefore, in patients with spinal cord abscesses, The genus Salmonella is typically not considered a likely pathogen, especially in the absence of typical symptoms. In this case, the limited information provided by traditional cultivation methods, particularly under the influence of antibiotics. However, next-generation sequencing (NGS) unexpectedly detected Salmonella, which assisted in formulating the final treatment plan. This underscores the role and clinical value of NGS in pathogen identification.